Decision and dopaminergic system: an ERPs study of Iowa gambling task in Parkinson’s disease - Mapelli, Daniela; Di Rosa, Elisa; Cavalletti, Matteo; Schiff, Sami; Tamburin, Stefano (Frontiers in Psychology, 2014)
Recent researches reported behavioural and emotional impairment in Parkinson’s disease (PD), even in the earliest stages. This impairment affects also decision-making and learning processes. The Iowa Gambling Task (IGT) is commonly used to examine the decision-making capacity. The purpose of the present study was to investigate the neural correlates of feedback evaluation in the decision-making process into a learning context, using IGT and event-related potentials (ERPs) in a group of non-demented medicated PD patients. Fifteen PD patients and 15 healthy controls were recruited for the study. PD patients were administrated a basic neuropsychological assessment oriented to exclude cognitive impairments. Both groups underwent the computerized IGT during electroencephalography (EEG) registration. To analyse ERPs, continuous EEG data were epoched within a time-window starting 1000 ms before and ending 1000 ms after feedback presentation and averaged separately for positive (i.e. win condition) and negative (i.e. loss condition) feedbacks. Behavioural data revealed a significant lower performance of PD patients (p<.05) compared with the controls. While controls demonstrated a correct feedback evaluation, PD patients did not show any learning, selecting more disadvantageous decks even in the last part of task. Furthermore, ERPs results revealed that controls showed a significant difference (p<.05) in ERPs morphology recorded after the win and the loss conditions, suggesting that positive and negative feedbacks were differently evaluated and processed. PD patients showed a different pattern: their ERPs morphology was the same for positive and negative feedback. Interestingly, our ERPs results suggest that in PD patients an incorrect evaluation of context-relevant outcomes could be the reason of a poor performance in decision-making tasks, and could explain cognitive and behavioural problems related to impulse control disorder.